The Implementation of the Regional Regulation of the Bangka Belitung Islands Province Number 8 of 2018 concerning Control of Pollution and Environmental Damage (Case Study of Environmental Pollution and Damage in Central Bangka Regency) - Ismodi Ismodi; Ibrahim Ibrahim; Komang Jaka Ferdian (Inovbook Publications, 2022)
Regional Regulation No. 8 of 2018 aims to protect the environment from pollution and damage in fulfilling the right to a good and healthy environment based on the 1945 Constitution of the Republic of Indonesia. The purpose of this study is to determine the implementation of Regional Regulation number 8 of 2018 in Bangka Regency. In the middle, many economic activities are sourced from the management of natural resources that can damage the environment. This study uses the theory of policy implementation by Merilee S. Grindle which consists of the content of the policy and the policy environment. The research method used is a case study approach, in collecting samples the researcher uses purposive sampling technique, as well as data collection techniques, namely interviews and documentation. The results of the study show that the implementation of Regional Regulation number 8 of 2018 in Central Bangka Regency has not been carried out properly, because it has not been in accordance with the objectives of the regional regulation in decision making, and has not been able to carry out the interests of the regional regulation in stopping pollution and environmental damage, and the strategy taken is not development-oriented. environmentally friendly and sustainable. The Environment Agency of Central Bangka Regency admits that it is difficult to overcome the illegal mining that has occurred in Central Bangka Regency which has occurred in the last 7 years. and the strategies taken are not environmentally sound and sustainable. The Environment Agency of Central Bangka Regency admits that it is difficult to overcome the illegal mining that has occurred in Central Bangka Regency which has occurred in the last 7 years. and the strategies taken are not environmentally sound and sustainable. The Environment Agency of Central Bangka Regency admits that it is difficult to overcome the illegal mining that has occurred in Central Bangka Regency which has occurred in the last 7 years.